Challenges in hemophilia care in Australia and New Zealand. (2nd November 2015) - Brown, S.A.; Phillips, J.; Barnes, C.; Curtin, J.; McRae, S.; Ockelford, P.; Rowell, J.; Smith, M.P.; Dunkley, S.
Abstract: Background: Health and life expectancy for people with hemophilia have improved significantly in recent years, but we face new challenges, especially in the context of resource-constrained health services. Aim: This paper aims to highlight such challenges and propose practical solutions. Methods: Nine hemophilia specialists from Australia and New Zealand reached consensus on areas of greatest need for improvement in hemophilia care in these countries, based on clinical experience and published data, and agreed on how to address these. Results: Demography, optimizing treatment and assessing treatment success were identified as broad areas of challenge which included: comorbidities in ageing patients; transitioning from pediatric to adult care; equity of care for remote populations; weight-based dosing in obese patients; tailoring prophylaxis; accurate diagnosis of acute joint pain; managing chronic arthropathy; providing psychosocial support; consistency in definitions and assessment; and quantifiable outcome measures. Practice points included increased cross-specialty coordination and including psychologists and rheumatologists as part of comprehensive care teams; close collaboration between pediatric and adult centers to facilitate transition of care; systems such as telehealth that ensure continuity of care for remote populations; using pharmacokinetic data to tailor therapy; rapid and accurate diagnosis of acute joint pain; using data from bleeding registries to assess treatment effects and help with service planning; and ensuring consistency through benchmarking and standardization of HTCs. Summary: Achieving treatment equity, optimal outcomes and cost savings may be possible through investing in national governance structures, expanding the comprehensive model of care and implementing innovative solutions tailored to local needs.